Endovenous ablation and surgery in great saphenous vein reflux: a systematic review and network meta-analysis of randomised controlled trials protocol - Siribumrungwong, Boonying (BMJ Open, 2019)
INTRODUCTION: Endovenous ablations are the new standard procedures for treatment of great saphenous vein reflux including endovenous laser ablation (EVLA), radio frequency ablation (RFA), endovenous steam ablation (EVSA), mechanochemical ablation (MOCA), cyanoacrylate injection and ultrasound-guided foam sclerotherapy (UGFS). EVLA and RFA have demonstrated similar anatomical success for short-term outcome, but results are controversial for longer term (≥5 years). Additional evidences from randomised controlled trials have been published. This study is, therefore, conducted to, directly and indirectly, compare outcomes among all procedures stratifying by short-term and long-term follow-up. METHODS AND ANALYSIS: Medline and Scopus will be searched from 2000 to September 2018 with predefined search strategy. Interventions of interest are open surgery (ie, saphenofemoral or high ligation (HL) with stripping) and endovenous ablations (ie, EVLA, RFA, EVSA, MOCA, cyanoacrylate injection and UGFS). The primary outcome is anatomical success. Two independent reviewers will select studies, extract data and assess risk of bias. Disagreement will be adjudicated by the third party. Outcomes will be directly pooled if there are at least three studies in that comparison. A fixed-effect model will be used unless heterogeneity is present, in which case a random-effect model will be applied. Sources of heterogeneity will be explored using meta-regression analysis, and sub-group analysis will be done accordingly. Publication bias will be assessed using Egger’s test and funnel plot. A network meta-analysis will be applied to indirect compare all interventions including RFA, EVLA, EVLA with HL, UGFS, UGFS with HL and HL with stripping. Probability of being best intervention will be estimated and ranked. Inconsistency assumption will be checked using a design-by-treatment interaction model. ETHICS AND DISSEMINATION: Ethical approval is not required for systematic review and network meta-analysis. The study will be published in a peer-reviewed journal. PROSPERO REGISTRATION NUMBER: CRD42018096794.